The Behavior of Waste Production and Waste Management During The Epidemic Situation of Coronavirus 2019 Among Students at Ubon Ratchathani University - ลิมปิทีปราการ, ปวีณา; ซุยน้ำเที่ยง, ชาลิณี; ทองสลับ, พัชรี; นาโสก, วริศรา; ทับทิมหิน, สง่า (Journal of Health Science of Thailand, 2023)
This research aimed to study the behavior of waste production and waste management that occurred during the epidemic situation of coronavirus 2019 among students in Ubon Ratchathani University, Thailang. It was mainly focused on waste generated from food delivery services and online ordering. The population in the study were 387 people selected by random sampling according to the proportion of students in each faculty. Data were collected by a set of questionnaire via Google Forms between September - October 2021; and the data were analyzed using descriptive statistics. The results showed that all students produced plastic bag waste; followed by plastic boxes/foam boxes (88.1 percent). Seasoning sauce packages were the most un-sorted waste material identified (covering 68.7 percent of the students). Boxes were sorted and kept for sale at 14.5 percent. Plastic glasses were sorted before being discarded at 28.9 percent. The average plastic bag production was 10.7 pieces per person per day (SD=11.5), and the maximum production was 150 pieces per week. The highest number of waste material was packaging bags and bubble bags with the maximum production of 200 pieces per month. The behavior that most of the samples did not practice was the bringing of a food box to contain food buying at the stores, 64.3 percent. The overall waste management behavior was at a moderate level, representing 70.5 percent of the students. Therefore, government agencies and shops should encourage students to use cloth bags and carry food boxes which is easy to do and can reduce the amount of plastic used by college students.